Effect of journal arrangement on load-bearing capacity of high-speed train axles - GUO Feng; LIU Jianxin; WU Shengchuan; CAI Jiufeng (机车电传动)
Theoretical models, finite element models and vehicle system dynamics models of both inside and outside journal high- speed train axles were established for the load-bearing capacity analysis, then the load-bearing states, stress distribution regularities and dynamic loads of these train axles were systematically studied. Result shows that the inside journal axles can achieve higher efficiency and utilization of the axle body, and the maximum combined bending moments are only half of the traditional outside journal axles, therefore, inside journal axles realize a great advantage in the lightweight design; compared with traditional outside journal axles, the critical safety positions of inside journal high-speed train axles transfer to transition positions on both sides of the journal; Compared with traditional outside journal axles, the novel inside journal axles can significantly alleviate the limit value of wheel-rail vertical force, and the limit value of wheel-axle lateral force is slightly higher, both are conductive to reducing the synthetic moments of the axles. In summary, the novel inside journal train axles is identified with a great application prospect for high-speed train vehicles.